2022
DOI: 10.1186/s12885-022-10442-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of chlorhexidine mouthrinse on prevention of microbial contamination during EBUS-TBNA: a randomized controlled trial

Abstract: Background Although endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a minimally invasive procedure, fatal infectious complications have been reported. However, adequate preventive strategies have not been determined. We aimed to investigate the effect of chlorhexidine mouthrinse on the prevention of microbial contamination during EBUS-TBNA. Methods In this single-center, assessor-blinded, parallel-group randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Correction: Effect of chlorhexidine Mouthrinse on prevention of microbial contamination during EBUS-TBNA: a randomized controlled trial Na Young Kim 1 , Jae Hyeon Park 2,3 , Jimyung Park 1 , Nakwon Kwak 1,4 , Sun Mi Choi 1,4 , Young Sik Park 1 , Chang-Hoon Lee 1 and Jaeyoung Cho Following publication of the original article [1], the authors reported errors in Figs. 2 and 3.…”
Section: Bmc Cancermentioning
confidence: 99%
“…Correction: Effect of chlorhexidine Mouthrinse on prevention of microbial contamination during EBUS-TBNA: a randomized controlled trial Na Young Kim 1 , Jae Hyeon Park 2,3 , Jimyung Park 1 , Nakwon Kwak 1,4 , Sun Mi Choi 1,4 , Young Sik Park 1 , Chang-Hoon Lee 1 and Jaeyoung Cho Following publication of the original article [1], the authors reported errors in Figs. 2 and 3.…”
Section: Bmc Cancermentioning
confidence: 99%